Joining the Uniate in the Orthodox Church (1839): Origins, course, consequences - Yuliya Khytrovsʹka (Українське Pелігієзнавство, 1999)
The current complex inter-confessional relations in Ukraine compel the researcher to address their origins. In view of this, the issue raised by us is of increased interest.